The Short-Term Effects of Sulfur Mustard Gas on the Complement System - AH Keyhani; MR Nowroozi (Tehran University of Medical Sciences, 2007)
Background: The serum levels of C3, C4, and the total hemolytic activity of complement system (CH50) of patients exposed to mustard gas (MG) in the battlefield were measured in this study. Methods: C3 and C4 were measured by single radial immunodifusion and CH50 was evaluated according to total hemolytic activity of the serum. Results:  The serum levels of C3 showed a significant increase on day 3 after exposure to MG. The serum levels of C3 in the sera of patients collected during 4-18 and 19-31 days after exposure to MG were also found to have increased significantly comparing to those of the controls. The levels of C4 in the sera of patients collected from the patients during 4-18 and 19-31 days after exposure were also found to be significantly higher than those of the controls. However the increase in the serum levels of C4 were not in the same magnitude as those of the C3. The serum CH50, which is a measure of the total hemolytic activity of classical complement system also showed a significant increase in patients' sera on day 3 and in the sera collected during 4-18 days after exposure. However, the CH50 in the sera of patients showed a decrease in the sera collected during 19-31 days after exposure to MG. Conclusion: Since C3 is an acute phase protein as well as a complement component, these results are discussed in terms of a vigorous acute phase response and activation of the complement system.